073 Hereditary spastic paraplegia caused by spastin (SPAST, SPG4) mutations is found more often in males: report of novel mutations from one centre, and review of published literature. Issue 3 (9th February 2012) - Proukakis, C; Moore, D; Labrum, R; Wood, N W; Houlden, H
Abstract : Background: Hereditary spastic paraplegia (HSP) is characterised predominantly by slowly progressive spastic paraparesis. Early reports yielded conflicting results concerning sex differences in severity and prevalence of HSP in general. Around 40% of autosomal dominant (AD) cases are due to mutations in the SPAST (SPG4) gene, encoding spastin. This generally leads to a "pure" phenotype. Patients and Methods: The records of all patients with a SPAST mutation identified through the Queen Square neurogenetics clinic were reviewed. All published reports of SPAST mutations where the sex of patients was given were subsequently analysed in order to determine whether there is male excess. Results: A total of 27 patients with SPAST mutations were ascertained (17 male, 10 female). Most patients had a "pure" phenotype, although mild peripheral neuropathy was sometimes present. The total number of patients with SPAST mutations was 22, as three mutations were present in more than one person. The mutations included 11 novel ones. One patient carried two adjacent missense mutations. The pathogenesis of a further novel missense variant is uncertain. The excess of males was confirmed by review of all 31 published studies where the sex of the patients was given. A significant excess of males was identified (ratio 1.29, p=0.0007). Conclusions: Our results are consistent with other reports of SPAST mutations mostly causing a pure HSP phenotype, although mild neuropathy does not exclude a SPAST mutation. The excess of males in our sample and in the literature suggests that penetrance or severity may be sex-dependent. This merits further investigation as it has important implications for counselling.